Simulations of heat transfer to solid particles flowing through an array of heated tubes. (June 2016) - Morris, A.B.; Ma, Z.; Pannala, S.; Hrenya, C.M.
Highlights: Novel receiver with solids as heat transfer fluid. New continuum model for multiphase heat transfer. Continuum model validated via DEM simulations. Abstract: A novel solar receiver that uses solid particles as a heat transfer fluid is being developed at the National Renewable Energy Laboratory for use in concentrating solar power plants. The prototype considered here is enclosed and contains arrays of hexagonal heat transfer tubes that particles flow between. Discrete element method (DEM) simulations were completed for a laboratory-scale solar receiver for different geometric configurations, hexagon apex angles, particle sizes, and mass flow rates. The heat transfer strongly depends on the particle size, where increased heat transfer is obtained using smaller particles. At higher solids mass flow rates, more particles contact the heat transfer surfaces and the overall heat transfer increases. When a sharper apex angle was used, the particles flow through the receiver at a faster velocity, but the heat transfer decreases because the solids concentration decreases slightly at higher velocities. The DEM simulations show that the heat transfer strongly depends on the solids concentration near the heat transfer surfaces as well as particle size. A new continuum model has recently been developed (Morris et al., 2015) that accounts for both of these effects, and it was previously tested for simple systems. In the current effort, the continuum model was applied to the complex solar receiver and validated via comparison to DEM data. The results indicate that the new continuum model accurately predicts the local heat transfer coefficient and yields an overall heat transfer coefficient with an average error less than 5%.